Mono- and dual-targeting triplebodies activate natural killer cells and have anti-tumor activity in vitro and in vivo against chronic lymphocytic leukemia. (1st September 2016) - Vyas, Maulik; Schneider, Ann-Charlott; Shatnyeva, Olga; Reiners, Katrin S.; Tawadros, Samir; Kloess, Stephan; Köhl, Ulrike; Hallek, Michael; Hansen, Hinrich P.; Pogge von Strandmann, Elke
ABSTRACT: Chronic lymphocytic leukemia (CLL) is the most common form of leukemia that affects B lymphocytes in adults. Natural killer (NK) cells in CLL patients are intrinsically potent but display poor in situ effector functions. NKG2D is an activating receptor found on NK and CD8 + T cells and plays a role in immunosurveillance of CLL. In this study, we developed mono- and dual-targeting triplebodies utilizing a natural ligand for human NKG2D receptor (ULBP2) to retarget NK cells against tumor cells. Triplebodies in both formats showed better ability to induce NK-cell-dependent killing of target cells compared to bispecific counterparts. A mono-targeting triplebody ULBP2-aCD19-aCD19 successfully triggered NK cell effector functions against CLL cell line MEC1 and primary tumor cells in allogenic and autologous settings. Additionally, a dual-targeting triplebody ULBP2-aCD19-aCD33 specific for two distinct tumor-associated antigens was developed to target antigen loss variants, such as mixed lineage leukemia (MLL). Of note, this triplebody exhibited cytotoxic activity against CD19/CD33 double positive cells and retained its binding features even in the absence of one of the tumor antigens. Further, ULBP2-aCD19-aCD19 showed significant in vivo activity in immune-deficient (NSG) mouse model transplanted with CLL cell line as target cells and human immune cells as an effector population providing a proof-of-principle for this therapeutic concept.